Vozes das juventudes: quando a escola pública e o feminismo se encontram - um estudo de caso do projeto Molhares - Moraes, Marina Guilherme Caselli (Universidade Federal de São Carlos, 2020)
This dissertation seeks to think and discuss interfaces between youths, education, feminisms and protagonisms, with a look turned mainly to processes of meaning and construction of identities, based on fieldwork carried out throughout 2019 in a public high school with students involved in a female and feminist project, which marked a new moment for a traditionally conservative institution with a history of intense gender conflicts. Expected with that, to contribute with the Human and Social Sciences in a perspective of critical education and a solidary society, committed to humans equity and diversity, starting from values such as responsibility and freedom and with the certain of education as a multiple and coproduced process between subjects in constant interaction
Youth voices: when the public school and feminism meet - a case study of the Molhares project
Keywords: Jovens mulheres; Feminismos; Protagonismos; Ensino médio; Young womens; Feminisms; Protagonisms; High school; CIENCIAS HUMANAS::EDUCACAO